2006
DOI: 10.1198/016214506000000302
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Dirichlet Processes

Abstract: We consider problems involving groups of data where each observation within a group is a draw from a mixture model and where it is desirable to share mixture components between groups. We assume that the number of mixture components is unknown a priori and is to be inferred from the data. In this setting it is natural to consider sets of Dirichlet processes, one for each group, where the well-known clustering property of the Dirichlet process provides a nonparametric prior for the number of mixture components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
3,034
0
16

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 2,703 publications
(3,058 citation statements)
references
References 42 publications
8
3,034
0
16
Order By: Relevance
“…The hierarchical Dirichlet process (HDP) (Teh et al [2006]) extends the DP to cases in which groups of data are produced by related, yet distinct, generative processes. Taking a hierarchical Bayesian approach, the HDP places a global DP prior DP(αG 0 ) on Θ, and then draws group specific distributions G j ∼ DP(αG 0 ).…”
Section: Background: Dirichlet Processes and The Sticky Hdp-hmmmentioning
confidence: 99%
See 4 more Smart Citations
“…The hierarchical Dirichlet process (HDP) (Teh et al [2006]) extends the DP to cases in which groups of data are produced by related, yet distinct, generative processes. Taking a hierarchical Bayesian approach, the HDP places a global DP prior DP(αG 0 ) on Θ, and then draws group specific distributions G j ∼ DP(αG 0 ).…”
Section: Background: Dirichlet Processes and The Sticky Hdp-hmmmentioning
confidence: 99%
“…It can be shown that the following finite, hierarchical mixture model converges in distribution to the HDP as L → ∞ (Ishwaran and Zarepour [2002], Teh et al [2006]):…”
Section: Background: Dirichlet Processes and The Sticky Hdp-hmmmentioning
confidence: 99%
See 3 more Smart Citations